The Journey to the South: A parable and five critiques - Muller, Stephanus (African Sun Media, 2019)
The Journey to the South grapples with the entanglement of ethics, aesthetics, disciplinary transformation, institutional decolonisation and modalities of protest at South African universities. Riffing on Herman Hesse’s short novel Die Morgenlandfahrt (Journey to the East), Stephanus Muller’s parable is systematically misunderstood in five different but overlapping critiques by the scholars Doctor Werner Ansbach, Proffessore Parvenu, Doctor Christian Grippenkerl, Professor Doctor Finkel Fenkel and an anarchic colloquium of shit-stirrers. Throughout the book, the art of Manfred Zylla celebrates the delirium of protest, fascist nightmares and geese in concert halls.